Regulatory Reforms for Health Facilities: Can These Suffice?; Comment on "What Lies Behind Successful Regulation? A Qualitative Evaluation of Pilot Implementation of Kenya's Health Facility Inspection Reforms" - Arthur Bagonza; David Musoke; Henry Wamani (Kerman University of Medical Sciences, 2023)
In their study on how Joint Health Inspections (JHI) were implemented in practice with a need to identify key facilitators or barriers for regulatory policy and practice, Tama et al found that innovative regulatory reforms markedly improved inspection scores among intervention health facilities albeit with challenges. Their article makes an important contribution to the body of knowledge in as far as regulation of health facilities is concerned. In low- and middle-income countries (LMICs), private health facilities are poorly regulated and yet, they purge gaps where public health facilities are inadequate as was demonstrated during the COVID-19 pandemic. Therefore, while regulation of public health facilities is standardized, the research by Tama and colleagues provides a unique opportunity to continue dialogue on how private health facilities can be regulated through inspection and supervision. Regulation of public and private health facilities continues to be contentious since both experience unique contextual challenges.